Loucura materna e a perversão materna: revisão de escopo - Spener Neto, João Bosco (Brasil, 2024)
Maternal role has been constructed in our society as something sacred, idealized, and fulfilling for women who have been socially, culturally, and historically shaped through performative acts. The image of the sanctified, good, and instinctive mother is quickly sold and distributed in our society as the sole way to experience motherhood. It is essential to emphasize that the excessive idealization of motherhood often hinders the dialogue about experiencing negative emotions and inherent conflicts in motherhood. This excessive idealization creates a smokescreen around "negative" motherhood, leading women who do not fit this idealized mold to be labeled as "crazy," with their caregiving being delegitimized. Exploring an understanding of mothers who exhibit perverse behaviors becomes challenging, as they are either stigmatized as "crazy" or diagnosed with psychological disorders. This study aimed to investigate perverse acts of mothers towards their children through a literature review. To do so, a scoping review was conducted using the databases of the Scientific Electronic Library Online (Scielo), the CAPES Periodicals Portal, and Electronic Journals in Psychology (Pepsic), resulting in the selection of 5 articles. The findings suggest that mothers displaying supposedly perverse behaviors have an ambiguous relationship with their children. The nature of the dyad is characterized by significant ambivalence of emotions, ranging from excessive affection to excessive violence or even maternal absence. Moreover, these mothers with perverse actions towards their children convey generational traumas that become integrated into their relationship with their babies.